4 - Towards a Bottom-up Approach for Localising SDGs in African Cities Findings from Cairo and Dar es Salaam - Nagati, Omar; Gad, Hanaa; El-Didi , Amin Ali; Kihila , Jacob M.; Mbuya , Elinorata; Njavike , Emmanuel (Africa Development, 2023)
This article attempts to apply a localisation methodology previously devel- oped by the authors to analyse the current status of the implementation and monitoring apparatuses for SDGs 6 (water and sanitation) and 11.2 (mobil- ity) in the case study cities – Cairo and Dar es Salaam. It uses comparative, top-down and grounded bottom-up analyses to identify gaps in the existing SDG framework and ultimately proposes a set of evaluation criteria to replace the global indicators with new localised and quantifiable indicators in the two cities. In doing so, it responds to prevalent critiques of SDGs specific to their application in the global South, including difficulties in measuring and monitoring urban conditions, misrepresentation due to the reduction of complex local conditions to abstracted data, and the inadequate capacity of the agenda to consider and assess informal activity. The proposed revisions to targets and indicators for SDG 6.1, 6.2 and 6.b, and SDG 11.2, were later discussed with community organisers and residents to bolster their validity, and represent a stepping stone towards negotiating better sustainable-development paradigms with Egyptian and Tanzanian policy-makers. More generally, these revisions invite further inquiries into other African cities or other geographies with a prominent urban informality in order to update the general SDG framework across its seventeen goals and develop locally embedded standards for different kinds of service provision and outcomes.